2011
DOI: 10.1038/cmi.2011.35
|View full text |Cite
|
Sign up to set email alerts
|

Activation of human fibroblast-like synoviocytes by uric acid crystals in rheumatoid arthritis

Abstract: Hyperuricemia-mediated uric acid crystal formation may cause joint inflammation and provoke the destruction of joints through the activation of inflammasome-mediated innate immune responses. However, the immunopathological effects and underlying intracellular regulatory mechanisms of uric acid crystal-mediated activation of fibroblast-like synoviocytes (FLS) in rheumatoid arthritis (RA) have not been elucidated. Therefore, we investigated the in vitro effects of monosodium urate crystals, alone or in combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
(62 reference statements)
1
21
0
Order By: Relevance
“…Increased SUA levels might elicit an inflammatory response in this matrix by the activated immunopathological mechanism, which is similar to that in gout joints, and then provoke the damage gradually in proportion to the exposure to high SUA levels throughout adult life . Experimental animal and in vitro studies have already suggested that uric acid was a biologically active compound that could increase inflammatory mediators known to lead to vascular damage either by the generation of reactive oxygen species and subsequent endothelial dysfunction or the induced endothelin‐1 secretion in vitro . The data revealing that these effects were reversed by the treatment with allopurinol (an XO inhibitor) also proved this inflammatory theory .…”
Section: Discussionmentioning
confidence: 97%
“…Increased SUA levels might elicit an inflammatory response in this matrix by the activated immunopathological mechanism, which is similar to that in gout joints, and then provoke the damage gradually in proportion to the exposure to high SUA levels throughout adult life . Experimental animal and in vitro studies have already suggested that uric acid was a biologically active compound that could increase inflammatory mediators known to lead to vascular damage either by the generation of reactive oxygen species and subsequent endothelial dysfunction or the induced endothelin‐1 secretion in vitro . The data revealing that these effects were reversed by the treatment with allopurinol (an XO inhibitor) also proved this inflammatory theory .…”
Section: Discussionmentioning
confidence: 97%
“…When we used canine synovial fibroblasts as a model for the study, the involvement of ERK and JNK MAPK pathways, but not of p38, on TNF-α-induced IL-8 expression was observed. In normal human synovial fibroblasts, TNF-α was demonstrated to induce IL-8 secretion and to activate ERK and JNK, but not p38 MAPK [ 53 ]. Therefore, TNF-α-induced activation of p38 MAPK related to IL-8 expression may occur in synovial fibroblasts of RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…DAMP molecules included high mobility group box 1 protein (HMGB1; R&D Systems, Minneapolis, MN), heat shock protein-60 (HSP-60; Enzo Life Sciences, Farmingdale, NY), and ATP (Sigma-Aldrich, St. Louis, MO). Uric acid (Sigma-Aldrich) crystals were prepared as described (9). Necrotic cell lysate was prepared from normal human lung PDGFR-␤-negative cells by subjecting 10 7 cells/ml to five successive freeze/thaw cycles.…”
Section: Methodsmentioning
confidence: 99%